ISTITHA’AH HEALTH IN THE FIQH PERSECTIVE HAJJ WORSHIP: VIEWED IN THE MASLAHAH MURSALAH ASPECT - Imamah, Ade Irma; Amrin, Amrin; Hidayat, Muhammad Faishal (MIZAN: JOURNAL OF ISLAMIC LAW, 2024)
This research aims to examine how Istitha’ah Health in the Hajj Pilgrimage is viewed in the aspect of Maslahah mursalah. This type of research uses a qualitative descriptive approach with normative juridical. The research results show that the Hajj pilgrims' health Istitha’ah must be based on the Republic of Indonesia Minister of Health Regulation Number 15 of 2016 by going through a series of health examination programs, including the first stage, second stage and third stage. Apart from that, the government is also implementing a health development program during the waiting period and departure period for Hajj pilgrims. The medical team or health management team for the Hajj pilgrims determines health Istitha’ah through a series of health checks. The first stage results in a diagnosis that is categorized as high health risk (risti) or not high risk (non-risti). The second stage determines the feasibility of Istitha’ah. The third stage is used to determine whether the Hajj pilgrims' health status is suitable for departure or not, referring to international aviation safety standards and/or international health regulations. From the perspective of Islamic law and Maslahah Mursalah, health guidance, both during the waiting period and during the departure period, is considered Maslahah Dlaruriyyah. This is related to providing convenience for fulfilling human needs, in accordance with the main principles in Islam, namely heredity, soul and reason. Thus, collaboration between the government and all elements is needed in efforts to provide outreach to Hajj pilgrims regarding comprehensive health Istitha’ah.